2013
DOI: 10.1093/ntr/ntt005
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Smoking Cessation Treatments Provided in HIV Clinical Care Settings

Abstract: introduction: Identifying successful smoking treatment interventions and methods of delivery is critical given the smoking rates among HIV-positive populations and the medical implications of smoking in this population. This study compared the efficacy of 3 smoking cessation interventions provided in HIV clinical treatment settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 46 publications
2
89
0
Order By: Relevance
“…16,17 People living with HIV are more likely to quit smoking if they are married, older, or employed, or have a low level of nicotine dependence or no mood disturbance. [18][19][20] These predictors of smoking cessation are similar to those found in the general population. On the other hand, predictors that are specific to people living with HIV include HAART use and CD4 cell count; yet, findings are inconsistent.…”
Section: Kim Et Alsupporting
confidence: 73%
See 1 more Smart Citation
“…16,17 People living with HIV are more likely to quit smoking if they are married, older, or employed, or have a low level of nicotine dependence or no mood disturbance. [18][19][20] These predictors of smoking cessation are similar to those found in the general population. On the other hand, predictors that are specific to people living with HIV include HAART use and CD4 cell count; yet, findings are inconsistent.…”
Section: Kim Et Alsupporting
confidence: 73%
“…On the other hand, predictors that are specific to people living with HIV include HAART use and CD4 cell count; yet, findings are inconsistent. [18][19][20] There are substantial gender differences in smoking behavior in terms of nicotine dependence and outcomes of smoking cessation. For example, men are more likely to be heavy smokers and more nicotine dependent compared to women.…”
Section: Kim Et Almentioning
confidence: 99%
“…53 All participants received NRT. Cessation rates at the end of treatment ranged from 15% to 29% across conditions, but treatment differences in abstinence were not statistically significant.…”
Section: Technology Assisted Interventionsmentioning
confidence: 99%
“…We excluded 13 additional studies for the following reasons: the outcome was not abstinence (4 studies), no control group (4 studies), follow-up less than four weeks (1 study), quasi-experimental study (1 study), face-to-face or mHealth interventions were not specified (1 study), zero smoking abstinence rate in both intervention and control groups, yields a computational error (1 study), and participants in the intervention arm received either mHealth or face-to-face interventions but not both (1 study). Hence, 10 RCTs met the inclusion criteria and included in the analysis [20][21][22][23][24][25][26][27][28][29] .…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Average age of the study population was 45 years (range: 42 to 50) and women comprised about 37% (range: 8% to 100%). Smoking cessation strategies were administered face-to-face in seven studies, [14][15][16][17][18]20,21 and sustained smoking abstinence estimates were reported in four studies. 14,[21][22][23] The intensity and maximum follow-up period ranged from 4 weeks to as much 52 weeks.…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%